2014
DOI: 10.3892/br.2014.313
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin as a potential biomarker for the differential diagnosis between lung cancer and lung infection

Abstract: Abstract. Satisfactory biomarkers for screening and early diagnosis of lung cancer remain scarce and require further investigation. The aim of the present study was to examine the changes of the biochemical and protein composition in the serum and pleural effusion from lung cancer and lung infection (bacterial pneumonia) patients. A total of 92 patients with lung cancer, 38 with bacterial pneumonia and 42 healthy controls were enrolled in the study. The serum levels of cholesterol, apolipoprotein A and transth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
5
0
1
Order By: Relevance
“…Previous research has shown the TTR level to be upregulated in the sera of adenocarcinoma lung cancer patients using 2̻DE and MALDI̻TOF̻MS peptide mass fingerprinting [18]. Another recently published Chinese population based study of patients with lung cancer found that both TTR levels in pleural effusion and pleural effusion to serum TTR ratios were higher compared with patients with noncancerous lung infections [19]. These results along with our findings indicate that TTR has the potential to contribute to differential diagnosis among different pleural effusions.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research has shown the TTR level to be upregulated in the sera of adenocarcinoma lung cancer patients using 2̻DE and MALDI̻TOF̻MS peptide mass fingerprinting [18]. Another recently published Chinese population based study of patients with lung cancer found that both TTR levels in pleural effusion and pleural effusion to serum TTR ratios were higher compared with patients with noncancerous lung infections [19]. These results along with our findings indicate that TTR has the potential to contribute to differential diagnosis among different pleural effusions.…”
Section: Discussionsupporting
confidence: 78%
“…TTR correlates with patient outcome in various diseases (6)(7)(8). With regard to lung cancer, TTR has been reported to be useful in distinguishing lung cancer from lung infection (9), and to be synthesized in lung cancer cells (10). Low perioperative serum TTR was reported to predict early recurrence after curative-intent surgery in NSCLC patients (11).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…Many types of proteomic biomarkers have been investigated for lung cancer detection, including Annexin II [ 122 ], APOA1 [ 123 ], carcinoembryonic antigen (CEA) [ 124 ], carbohydrate antigen 125 (CA125) [ 125 ], carbohydrate antigen 19-9 (CA19-9) [ 126 ], cytokeratin fragment 21-1 (CYFRA21-1) [ 127 ], CD59 glycoprotein [ 128 ], transthyretin (TTR) [ 129 ], GM2 activator protein (GM2AP) [ 130 ], haptoglobin-R2 [ 131 ], Ig-free light chain [ 132 ], neuron-specific enolase (NSE) [ 133 ], nitrated ceruloplasmin [ 134 ], plasma kallikrein B1 [ 135 ], ProGRP [ 136 ], retinol binding protein (RBP) [ 137 ], squamous cell carcinoma (SCC) [ 138 ], vascular endothelial growth factor (VEGF) [ 139 ], TPA [ 140 ], and tumor M2-pyruvate kinase [ 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%